EDUKASI NORMALISASI AIR SUNGAI PASKA BANJIR UNTUK KEPERLUAN RUMAH TANGGA DI TALUAK TIGO SAKATO MENGGUNAKAN ECO ENZYME - Dewi, Nadia Purnama; Ade Teti Vani; Dessy Abdullah; Irwan Triansyah; Aryaldy Zulkarnaini; Vina Tri Septiana (Nusantara Hasana Journal, 2025)
Eco-enzyme is a fermented product made from organic materials such as fruit and vegetable waste, brown sugar, and water. It is known to break down organic materials and effectively reduce pollutants. This community service activity aims to restore river water quality after flooding and enable water reuse for domestic use using eco enzymes. This program was implemented by involving local communities in the production process and application of eco-enzymes in Kenagarian Taluak Tigo Sakato, Batang Kapas, Pesisir Selatan, where flooding often occurs. Efforts included counselling and practical training on the benefits and methods of making eco-enzymes and the application of eco-enzymes to the use of water for household purposes by residents. Water quality was evaluated by measuring parameters such as pH, turbidity, organic matter content, and the presence of pathogenic microorganisms before and after the application of eco-enzyme. The results showed that the quality of river water used for domestic purposes improved significantly, with lower organic matter content and turbidity, and a decrease in the number of pathogenic microorganisms. This measure improved the river water quality and enabled the community to protect the environment and deal with post-flooding problems independently and sustainably.